The Sustainability of Livestock Gaduh System in Islamic Economics: The Role of Social Capital, Mudharabah, and Circular Economy - Erdianto, Rikidwi; Latief, Nur Fitry; Sonu, Sri Sunarni (Maqrizi: Journal of Economics and Islamic Economics, 2025)
Traditional economic systems, such as livestock farming in rural areas, are generally studied normatively in the perspective of Islamic law, thus underemphasizing their empirical dynamics as an instrument of adaptive economic resilience. This study aims to analyze the fundamental factors of the sustainability of the Gaduh system in Sidodadi Village, North Bolaang Mongondow Regency, as well as its contribution to increasing income and environmental sustainability. The research uses a qualitative method with a field descriptive approach. Data were collected through in-depth observation and interviews of purposively selected key informants based on their experience and active involvement in the disputed contract. The data is then analyzed through the stages of reduction, display, and conclusion. The results show that the sustainability of the intergenerational Gaduh system does not depend on the strength of formal contracts, but is supported by strong social capital, especially trust and personal reputation, which serves as a substitute for formal collateral. Substantively, Gaduh practices are in line with the principle of mudharabah, where the risk of material losses due to natural factors is borne by the capital owner (shahibul maal), while the manager (mudharib) bears the risk of energy and time. From an economic perspective, the Gaduh system acts as a social safety net that provides a strategic lump-sum income to finance the long-term needs of households. Another important finding is the formation of a local circular economy ecosystem through the use of livestock waste as organic fertilizer, which reduces agricultural production costs and supports the principle of environmental conservation (hifz al-bi'ah). This study recommends the integration of the Gaduh system in village economic empowerment policies through managerial assistance and risk mitigation without eliminating local wisdom.